2016
DOI: 10.1007/s00018-016-2397-5
|View full text |Cite
|
Sign up to set email alerts
|

CREB decreases astrocytic excitability by modifying subcellular calcium fluxes via the sigma-1 receptor

Abstract: Astrocytic excitability relies on cytosolic calcium increases as a key mechanism, whereby astrocytes contribute to synaptic transmission and hence learning and memory. While it is a cornerstone of neurosciences that experiences are remembered, because transmitters activate gene expression in neurons, long-term adaptive astrocyte plasticity has not been described. Here, we investigated whether the transcription factor CREB mediates adaptive plasticity-like phenomena in astrocytes. We found that activation of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The Sigmar1 gene has a CREBbinding site in its promoter region; METH-mediated activation of astrocytes involved CREB translocated into the nucleus and interaction with the promoter of Sigmar1, resulting in increased expression of Sigmar1 66 . Similarly, Sigmar1 upregulation was observed in cultured astrocytes from adult rats after infection with the VP16-CREB viral vector, and in transgenic mice with targeted activation of CREB in astrocytes 67 . All of these studies suggest a CREB-Sigmar1 feedback loop regulating their own expression modulated by METH exposure.…”
Section: Discussionmentioning
confidence: 81%
“…The Sigmar1 gene has a CREBbinding site in its promoter region; METH-mediated activation of astrocytes involved CREB translocated into the nucleus and interaction with the promoter of Sigmar1, resulting in increased expression of Sigmar1 66 . Similarly, Sigmar1 upregulation was observed in cultured astrocytes from adult rats after infection with the VP16-CREB viral vector, and in transgenic mice with targeted activation of CREB in astrocytes 67 . All of these studies suggest a CREB-Sigmar1 feedback loop regulating their own expression modulated by METH exposure.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, a recent study in isolated mitochondria has revealed comparable oxidative phosphorylation in astrocytes and neurons, despite molecular differences in ETC complexes (Lopez-Fabuel et al, 2016). And, finally, astrocyte mitochondria have an active role in calcium signaling (Agarwal et al, 2017;Eraso-Pichot et al, 2017). This is a key element of astrocyte excitability, mediating astrocyte actions in the so-called cerebrovascular unit that controls the coupling of brain metabolism with blood flow (Belanger et al, 2011).…”
mentioning
confidence: 99%
“…The AGC1 promotor regions contain a CRE site, which in neurons leads to increased AGC1 expression after binding of CREB upon its calcium-induced phosphorylation (Menga et al, 2015). CREB-dependent transcription additionally upregulates Sigma-1 receptor expression, and leads to lowered astrocytic excitability by decreasing ATP-dependent subcellular calcium waves (Eraso-Pichot et al, 2017). ATF4 is another CREB protein.…”
Section: Signaling Pathways Interact With Mitochondrial Functioning Imentioning
confidence: 99%